Utilization of slaughterhouse by-products: a current scenario in Dhaka city - Abdulla, Md Shefath; Islam, Md Saiful; Kabir, Md Enayet; Dadok, Falguni; Zaber, Md Abdullah Al; Sarkar, Shikha (Asian Journal of Medical and Biological Research, 2021)
Slaughter-houses are the places from where people get the meat for consumption, but the time is to utilize the by-products to increase the GDP’s rate from livestock. A field survey was conducted regarding usage of the by-products of slaughterhouses and/or meat selling centers in Dhaka city of Bangladesh. Data were collected from total 60 slaughterhouses and/or meat selling centers randomly from different part of Dhaka city consisting 20 large animal (cattle, buffalo), 20 small animal (goat, sheep) and 20 poultry bird (chicken, duck) slaughterhouses and/or meat selling centers. Following slaughtering process huge amount of different by-products are also produced that have good economic and nutritive value. The results revealed that edible by-products such as head trimmings, brain, tongue, heart, stomach, lungs, liver, pancreas, spleen, kidney and tail were used by 100% as human food. Inedible by-products had diversified uses but to some extent they were also rejected. However, no one of the inedible by-products was fully rejected. Among the inedible by-products the hides had a great industrial value. Poultry by-products like blood, intestines and feather wastes were generally found to utilize as fish feed. Most slaughterhouses were found to maintain moderate to poor hygienic conditions where very few maintained good condition. Almost two-third (61.67%) slaughterhouses were used water container as water supply followed by hose pipe (33.33%) and tape water (5%) for cleaning purpose. It can be concluded that by-products are valuable materials but due to lack of management and industrial mind slaughterhouses of the Dhaka city cannot utilize those materials. Therefore, proper usages of by-products can run a new prospective business in Bangladesh. Asian J. Med. Biol. Res. December 2020, 6(4): 809-816